Zero valent iron produces dichloroacetamide from chloramphenicol antibiotics in the absence of chlorine and chloramines. (1st November 2016) - Chu, Wenhai; Ding, Shunke; Bond, Tom; Gao, Naiyun; Yin, Daqiang; Xu, Bin; Cao, Zhongqi
Abstract: Dichloroacetamide (DCAcAm) is an important type of nitrogenous disinfection byproduct. This study is the first to report that DCAcAm can be formed in the absence of chlorinated disinfectants (chlorine and chloramines). This can occur through reduction of three chloramphenicol (CAP) antibiotics by zero valent iron (ZVI). The effects of key experimental parameters, including reaction time, ZVI dose, pH, temperature, water type, and the presence of humic acid (HA) on the formation of DCAcAm were ascertained. The DCAcAm yields from three CAPs all presented the trend of increasing first and then decreasing with time and also increased with increasing ZVI dosage. DCAcAm yields from the ZVI reduction route were higher than those resulting from the chlorination of some previously identified DCAcAm precursors. Acidic conditions favored the formation of DCAcAm by the ZVI route. In addition, lower temperatures increased DCAcAm yields at extended contact times (>12 h). DCAcAm formed from the three CAPs in the presence of HA was lower than in the absence of HA. The formation potential of DCAcAm from the reduction of authentic waters spiked with CAPs by ZVI showed good linear correlations with initial concentrations of the three CAPs. This allows the formation of DCAcAm from the reduction of CAPs by ZVI to be predicted. Given that many wastewater and drinking water distribution networks contain unlined cast iron pipes, reactions between CAPs and ZVI may contribute to the formation of DCAcAm in such systems. Graphical abstract: Highlights: ZVI reduces antibiotic CAPs to form dichloroacetamide (DCAcAm) in water. DCAcAm yields from CAP reduction by ZVI were higher than from chlor(am)ination. Lower pH and temperatures favored DCAcAm formation by ZVI. DCAcAm formation from reduction of CAPs was inhibited in the presence of HA. DCAcAm formation in authentic waters spiked with CAPs was predicted.